A new system for detection of thermoluminescence and delayed luminescence from photosynthetic apparatus with precise temperature control. Issue 2 (2002) - Noguchi Noguchi, Takumi Takumi; Katoh Katoh, Masaya Masaya; Inoue Inoue, Yorinao Yorinao
Abstract : A new system for thermoluminescence (TL) and delayed luminescence (DL) measurements with precise temperature control was developed. A freezing/heating stage for microscope was modified to afford a fixed sample temperature and a constant heating rate. A valve equipped with a low‒flow bypass for cold N2 gas through liquid N2 was used for both fine control of the sample temperature and for rapid cooling of the sample after flash illumination. High performance of the system was demonstrated by measurements of the TL glow curves with various heating rates and the DL decays at different temperatures arising from recombination of charged pairs in photosystem II membranes.